Preparation and Evaluation of Inflammation Targeted Nano-micellar Formulation of Celecoxib - Bahadori, Fatemeh; Buyuk, Ayse Seyma; Kozanoglu, Ahmed Serdar; Eskandari, Zahra; Ankarali, Handan; Kepekci Tekkeli, Serife Evrim; Nur Kaleli, Humeyra; Kocyigit, Abdurrahim (GALENOS PUBL HOUSE, 2019)
Objective: Celecoxib (CLX), brand named Celebrex, which belongs to non-steroidal anti-inflammatory drugs family, selectively inhibits the cytokine related cyclooxygenase-2 isoenzyme and thus, possesses less gastrointestinal side effects, have shown to cause stroke, myocard infarction and even death in some cases. In this study we aimed to target inflammation site using CLX uploaded nano-micelles (nano-CLX) made of poly (lactic-co-glycolic) acid (PLGA) to protect other tissues from its side effects. Methods: CLX was physically entrapped in PLGA micelles using w/o/w emulsion method, resulted in obtaining mono-dispersed particles with 112 nm size. 50 mg PLGA was able to carry 50 mg CLX in 20 mL (2.5 mg/mL) with encapsulation efficiency of 85%. Rheumatoid arthritis model was achieved by injection of complete Freund's Adjuvant to the hint paw of Wistar rats. Infected groups received oral Celebrex, intravenous (i.v.) Celebrex and nano-CLX. Each group was compared with a healthy control group receiving the drug via the same routes. The obtained serums and the hint paw sizes were studied for 6 hours in 3 time periods. Results: Prostaglandin E2 and tumor necrosis factor-a levels were found to be decreased for longer time period by application of nano-CLX compared to oral and i.v. Celebrex. Interleukin-1 (IL-1) and IL-6 levels showed a dramatic decrease at orally administered Celebrex groups, showing the accumulation of these pro-inflammatory Factors at inflammation area. Conclusion: Based on the hypothesis that the ratio of blood parameters is inversely proportional to accumulation at inflammation site, thus, our nano-formulation is targeted to the tissues in the systemic blood flow and have a better selective inhibition.
Keywords: Targeted inflammation therapy; Celecoxib; nano drug delivery system; PLGA; COX2; NONSTEROIDAL ANTIINFLAMMATORY DRUGS; BIODEGRADABLE POLYMERS; RHEUMATOID-ARTHRITIS; HPLC METHOD; NANOPARTICLES; POLYLACTIDE; COX-1; RISK; General & Internal Medicine